In the parable of Good Samaritan: The relevance of the absent - de Meneses, Ramiro Délio Borges (Vox Scripturae - Revista Teológica Internacional, 2018)
We seek, in this article, the sense of the moral spectacle, lived at the clinic, the relevance of the absent and how they mark the moral life. Thus, referring to Kant: men are, in genere, much better actors as more civilized. They take the mere appearance of affection, respect for others, modesty, lack of interest, not fooled by anything. May end up waking virtues, whose mere appearance they merely pretend. Therefore, the relevance of the missing may mark the clinical life, giving him a moral connotation. In fact, the parable of Good Samaritan shows many relevancies from plesiological to soteriological, which has its epicenter in the splancnofanic relevance.